Intraepidermal Epidermotropic Metastatic Melanoma: a Clinical and Histopathological Mimicker of Melanoma in Situ Occurring in Multiplicity - Lestre, S (2012)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2012-07-27T14:57:20Z No. of bitstreams: 1 J Cutan Pathol 2011 514.pdf: 1046519 bytes, checksum: f08eb3db16b837f6fda04e267744f3ab (MD5)